The law of nuisance in Malaysia - the problem and possibility / Azuriah Mohammad - Mohammad, Azuriah (Faculty of law, 1987)
NUISANCE is one branch of TURIS which is existed and happened in our every day life. Thus, when the word 'Nuxsance‘ appears, it rings a bell on the writer‘s mlnd, of a mischxef kind of activity. This led to the writer memory of an irritating incident that had happened in her hometown. Every Saturday nights. the writer’s family and the neighbourhood will be haunted by the sound of heavy machine motors which caused disturbance in the enjoyment of watchlng T.V. for a quiet and peaceful evenlng.